Action of CMG with strand-specific DNA blocks supports an internal unwinding mode for the eukaryotic replicative helicase - Lance Langston; Mike O’Donnell (eLife, 2017)
Replicative helicases are ring-shaped hexamers that encircle DNA for duplex unwinding. The currently accepted view of hexameric helicase function is by steric exclusion, where the helicase encircles one DNA strand and excludes the other, acting as a wedge with an external DNA unwinding point during translocation. Accordingly, strand-specific blocks only affect these helicases when placed on the tracking strand, not the excluded strand. We examined the effect of blocks on the eukaryotic CMG and, contrary to expectations, blocks on either strand inhibit CMG unwinding. A recent cryoEM structure of yeast CMG shows that duplex DNA enters the helicase and unwinding occurs in the central channel. The results of this report inform important aspects of the structure, and we propose that CMG functions by a modified steric exclusion process in which both strands enter the helicase and the duplex unwinding point is internal, followed by exclusion of the non-tracking strand.